Association between Bone Mineral Density and Body Composition in South Indian Rheumatoid Arthritis Patients: A Cross Sectional Study - Snekhalatha, U.; Anburajan, M. (Aktuelle Rheumatologie, 2013)
The aim of the present study was to compare and correlate body composition measurements and bone mineral density in patients with rheumatoid arthritis (RA) and age-matched controls to identify the possible prediction factors for low bone mass, and body composition changes.92 RA patients and 92 age- and sex-matched healthy controls were included for the study. The following assessments as well as measurements were carried out in each individual in a standard way: i) health assessment questionnaire (HAQ) score, ii) disease activity score (DAS-28), iii) forearm ulna bone mineral density (BMD) using dual energy x-ray absorptiometry (DXA), iv) estimated heel BMD using quantitative ultrasound, v) body composition parameters using bioelectrical impedence analysis, and vi) blood analysis using biochemical methods.Body fat mass (BFM) differed significantly between RA patient group (26.37±10.05 (kg)) and normal controls (30.11±8.64 (kg), <0.05). The Fat free mass (FFM) was also significantly different between RA patients (37.63±9.82 kg) and controls (42.97±6.68 kg, p<0.01). Forearm BMD and estimated heel BMD was significantly higher in controls (0.377±0.04 g/cm2; 0.493±0.08 g/cm2), than in RA patients (0.320±0.13 g/cm2, 0.452±0.10 g/cm2; p<0.01 and p<0.05, respectively). The Fat free mass (FFM), muscle mass (MM), segmental muscle mass (SMM) were significantly correlated with the estimated heel BMD as well as forearm BMD.These findings indicated that the body composition measurements might be useful for predicting bone mineral density (BMD) in RA patients. High RA activity was found to be associated with reduced function, and altered body composition and BMD.
Keywords: body composition analysis; bone mineral density; health assessment questionnaire; quantitative ultrasound; rheumatoid arthritis